2004
DOI: 10.1080/09273970490515874
|View full text |Cite
|
Sign up to set email alerts
|

A study of pre-school vision screening tests' testability, validity and duration: do group differences matter?

Abstract: Vision screening was performed on 268 pre-school children: 170 from a private pre-school, 33 from a Caribbean-American parochial pre-school and 65 pre-school children from a clinic serving indigent Spanish farm-workers. Using a multi-station format, a stereoacuity test and two visual acuity tests were performed during a single screening session. The time it took to complete a test was recorded. To pass the screening, children were required to pass one visual acuity test and the stereoacuity test. Children who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…10,11,15,16,27,28 Although the Sydney Paediatric Eye Disease (SPED) Study 27 showed an overall higher testability for the Lang-Stereotest II, only children younger than 30 months were administered the Stereo Smile II, whereas children of all ages (aged 6 to 72 months) were administered the Lang-Stereotest II. It is also not clear whether the actual SPED test procedure used for the Stereo Smile II included the use of the Demonstration Card (A) or a shortened format.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,15,16,27,28 Although the Sydney Paediatric Eye Disease (SPED) Study 27 showed an overall higher testability for the Lang-Stereotest II, only children younger than 30 months were administered the Stereo Smile II, whereas children of all ages (aged 6 to 72 months) were administered the Lang-Stereotest II. It is also not clear whether the actual SPED test procedure used for the Stereo Smile II included the use of the Demonstration Card (A) or a shortened format.…”
Section: Discussionmentioning
confidence: 99%
“…70,91 About one-third of the studies included participants younger than 3 years. 48,56,65,66,71,72,[75][76][77]80,81,85,88,91 The included studies reported accuracy of tests for a variety of target conditions, ranging from very specific (eg, astigmatism) to broad (eg, amblyopia risk factors). The prevalence of target conditions was generally much higher in samples from ophthalmology clinics 53,56,57,62,66,68,69,72,75,77,80,81,85,88 than in those from primary care, community, Head Start, or school settings.…”
Section: Accuracy Of Screening Testsmentioning
confidence: 99%
“…Vision screenings currently used in preschool children often include eye alignment testing to detect strabismus and binocularity problems 7,9,[12][13][14][15][16][17] and it is important to consider the effect of adding a test of ocular alignment on sensitivity for specifically detecting strabismus. While the goal of combining tests is often to increase sensitivity, the possible disadvantage of increasing false positives and unreadable or uninterpretable rates and costs must also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Phase II of the VIP Study showed that combining a test of stereopsis with a test of VA or refractive error did not improve sensitivity for detecting one or more targeted conditions. 11 However, vision screenings currently used in preschool children often include eye alignment testing to detect strabismus and binocularity problems 7,9,[12][13][14][15][16][17] and the effect of including a test of ocular alignment on sensitivity for specifically detecting strabismus has not yet been determined. Therefore, the purpose of this study was to determine the effect of combining tests of eye alignment with tests of refractive error or VA (which performed best overall in identifying preschool children with one or more targeted conditions) on sensitivity for detecting strabismus in preschool children.…”
mentioning
confidence: 99%